An empirical assessment of tourism development and planning in Nigeria: A Sustainability approach - Nnabuogor, Onyinye Onyekachukwu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Tourism development is most desirable when it is anchored on sustainability for the benefit of present generation without compromising its value for the future generations. Tourism industry, which is regarded as one of the fastest growing industry, if properly planned and managed, could generate huge revenue, employment, and other benefits. However, for this to be realized, it should not remain in the hands of parties with a laissez-faire approach. The focus of this study is Delta State/Nigeria tourism board with an aim to explore and examine the planning processes of tourism in the context of sustainable approach. A qualitative research method is applied to investigate the topic through in-depth interview with staff of Delta state tourism board. The study revealed that the pace of tourism awareness and development are still at its embryonic stage. Furthermore, the study discovered that bureaucratic bottle neck is also hampering the process of planning without considering the sustainability issues. In the meantime, lack of consensus on a general strategic plan was responsible for lack of proper performance of the industry. Recommendations are suggested how to initiate a strategic planning process and its implementation. Limitations and suggestions for further research are also elaborated. Keywords: Tourism Planning, Development issues, Sustainable Tourism, Tourism Strategies, case of Nigeria.

Öz: Turizm gelişimi, gelecek kuşaklar için değerine ödün vermeyerek, mevcut neslin yararına sürdürülebilirliği üzerine bağlantılı olduğu zaman en çok arzu ediliyor. En hızlı büyüyen endüstriden biri olarak kabul edilen turizm endüstrisi, düzgün planlanıp yönetilirse, büyük gelir, istihdam ve diğer yararlar yaratabilir. Bununla birlikte, bunun gerçekleşebilmesi için, lassie-fair yaklaşımı kullanan partilerin elinde kalmamalıdır. Bu çalışmanın odak noktası, Sürdürülebilir yaklaşımına bağlı turizmin planlama süreçlerini keşfetmek ve incelemek amacıyla, Delta Eyaleti / Nijerya Turizm Kuruludur. Konuyu derinlemesine incelemek için nitel bir araştırma Delta eyalet turizm kurulunun personeli ile görüşme yöntemi uygulanmaktadır. Araştırma, turizm ile farkındalık ve gelişme hızı hala embriyonik aşamadadır. Ayrıca, çalışma, bürokratiğinin darboğazlığı sürdürülebilirlik sorunlarını dikkate almadan planlama sürecini de engellediğini keşfetti. Bu arada, genel bir stratejik plan konusunda fikir birliğinin eksikliği endüstrinin uygun performansının eksikliğinden sorumluydu. Öneriler, stratejik bir planlama sürecinin başlatılması ve uygulanması için tavsiye edilir. Daha ileri araştırmalara yönelik sınırlamalar ve öneriler de ayrıntılarıyla ele alınmıştır. Anahtar Kelimeler: Turizm Planlaması, Kalkınma konuları, Sürdürülebilir Turizm, Turizm Stratejileri, Nijerya vakası.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2016. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Nigeria; Tourism Policy; Planning; Development Issues; Sustainable Tourism; Tourism Strategies; Case of Nigeria